2009
DOI: 10.1532/hsf98.20091127
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Microembolic Signals with a Single-Clamp Strategy in Coronary Artery Bypass Surgery: A Pilot Study

Abstract: Background: Neurologic defi cits are perhaps the most feared form of adverse outcome following cardiac surgery. Aortic trauma generates emboli and hence harbors the potential for neurocognitive injury. The single aortic clamp strategy of coronary artery bypass grafting (CABG) aims at reducing aortic manipulation. We hypothesized that this strategy will lead to a reduction in the number microembolic signals (MES) evaluated by transcranial Doppler (TCD), a surrogate measure of cerebral embolism.Methods: This pil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The stroke is mainly caused by microthrombus, it is thought that reducing aortic manipulation can reduce the microthrombus and protesting from stroke. [ 9 , 25 ] Moreover, it is reported that inflammation not only contributes to stroke pathogenesis but also has a possible association with outcome in acute ischemic cerebrovascular syndromes. [ 26 29 ] Clamping strategy may contribute to postoperative stroke by promoting inflammation, but the relationship between stroke and clamping strategy remains further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The stroke is mainly caused by microthrombus, it is thought that reducing aortic manipulation can reduce the microthrombus and protesting from stroke. [ 9 , 25 ] Moreover, it is reported that inflammation not only contributes to stroke pathogenesis but also has a possible association with outcome in acute ischemic cerebrovascular syndromes. [ 26 29 ] Clamping strategy may contribute to postoperative stroke by promoting inflammation, but the relationship between stroke and clamping strategy remains further investigated.…”
Section: Discussionmentioning
confidence: 99%